Derecho Constitucional y reelección de magistrados del Poder Judicial - Romero-Pérez, Jorge Enrique (2013)
This article explains the procedures for the reelection of Magistrates of the Judicial Branch. It is about the relationship between Constitutional Law and the authority of the Legislative Branch to appoint Magistrates.